The Effect of Lifestyle on Financial Management: The Moderating Role of Financial Literacy among Millennial Workers in Sukabumi City - Khaerunnisa, Salma; Norisanti, Nor; Komariah, Kokom (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study investigates the influence of lifestyle on financial management and examines the direct and moderating roles of financial literacy among millennial workers in Sukabumi City. A total of 155 respondents were selected using purposive sampling. Data analysis was conducted using path analysis with the bootstrapping method through SmartPLS 3.2.9 software. The findings reveal that lifestyle has a positive and significant effect on financial management. Similarly, financial literacy shows a positive and significant influence on financial management. Furthermore, financial literacy demonstrates a moderating effect by weakening the relationship between lifestyle and financial management, as indicated by a significant negative interaction effect. These results imply that enhancing financial literacy can help mitigate the potential adverse effects of an excessive lifestyle on financial management. This suggests the importance of integrating financial education programs into workplace development initiatives targeting millennials.